Analisis Kualitas Pelayanan Statistik Terpadu terhadap Kepuasan Pengunjung di Perpustakaan BPS Provinsi Sumatera Barat - Candra, Yuni; -, Rudi -; -, Febriani - (Manajemen dan Kewirausahaan; Vol 6 No 2 (2015): Published in May 2015, 2015)
The purpose of this study was to determine the reliability, responsiveness, assurance, empathy and physical evidence to the satisfaction of visitors as well as to analyze the reliability, responsiveness, assurance, empathy and tangibles together to visitor satisfaction in the library BPS West Sumatera Province. As for the reply to be sampled in this study is library visitor BPS West Sumatera Province, amounting to 100 respondents. Based on these results it appears that the reliability of the variables significantly influence visitor satisfaction with regression value of 0,254 with a significance level of 0,048 or < 0,05. Variables responsiveness did not significantly influence visitor satisfaction at -0,026 with a significance level of 0,784 or > 0,05. Variables guarantee does not significantly influence visitor satisfaction is 0,203 with a significance level of 0,197 or > 0,05. Empathy variables significantly influence visitor satisfaction with regression value of 0,234 with a significance level of 0,025 or < 0,05. While physical evidence variable does not significantly influence visitor satisfaction by 0,169 with a significance level of 0,172 or > 0,05. In the F test is seen that F count > F table (15,804> 2,311) with a significance level of 0,000 or < 0,05 consequently H 0 is rejected and H 1 is accepted which means that the variable reliability, responsiveness, assurance, empathy and tangibles together influential significant impact on visitor satisfaction. The coefficient of determination (adjusted R 2 ) of 0,428 meaning that 42,8% visitor satisfaction is affected by reliability, responsiveness, assurance, empathy and tangibles and 57,2% influenced by other factors.